Ritual Salai Jin: Sistem Pengobatan Tradisional di Kelurahan Ome - Sillia, Fadilah; Husain, Fadly (Umbara, 2023)
Traditional medicine has been utilized by people in several parts of Indonesia until today. Ritual Salai Jin is one among the traditional medicines. It has been practiced by people in North Maluku. This practice take the form of a ritual which involves a therapeutic method using mantras and prayers. This study aims to describe the ritual of medication using Salai Jin ritual; the stages of the process, symbolic meanings, and the effectiveness of the ritual as part of healing process. Employing a qualitative method, data for this research were gathered through observation, interviews, literature review, and documentation. The findings of study suggests that the practice of the Salai Jin ritual serves as a therapeutic modality which consists of different stages of ritual. The ritual, overall, does not merely serves as medication process. It is full of symbols and meaning which are important for Ome culture and demonstrates the health belief and health culture of the Ome people. Keywords: Ome Village, Salai Jin, traditional medicine